1989
DOI: 10.1139/b89-402
|View full text |Cite
|
Sign up to set email alerts
|

The effect of added nitrogen and phosphorus on mycorrhizal growth response and infection in Allium schoenoprasum

Abstract: The effect of different levels of phosphorus and nitrogen on mycorrhizal growth response and infection was studied using Allium schoenoprasum and Glomus caledonium. Nitrogen was added as ammonium or nitrate salt. Both the level of soil phosphorus and the level of nitrogen added affected the mycorrhizal growth response, which was greatest at intermediate levels of P and N. The nitrogen source did not affect the mycorrhizal growth response. At low levels of soil P, nitrogen addition did not affect mycorrhizal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Many studies show that the relative amounts of both N and P determine mycorrhizal function and support the predictions of the trade balance model (e.g. Bååth & Spokes, 1989; Sylvia & Neal, 1990; Valentine et al. , 2001; Azcón et al.…”
Section: Trade Balance and Thresholds In The Am Marketplacementioning
confidence: 69%
“…Many studies show that the relative amounts of both N and P determine mycorrhizal function and support the predictions of the trade balance model (e.g. Bååth & Spokes, 1989; Sylvia & Neal, 1990; Valentine et al. , 2001; Azcón et al.…”
Section: Trade Balance and Thresholds In The Am Marketplacementioning
confidence: 69%
“…N deposition also had a negative eVect on PLFA 16:1 5 when a narrower pH interval was analysed (Table 2). AM abundance is most strongly regulated by P availability to the plant, but N addition to soil in combination with good P availability has previously been found to reduce AM colonisation in pot cultures (Bååth and Spokes 1989) and AM biomass in the Weld (Johnson et al 2003). However, we could not evaluate whether P availability inXuenced the eVect of N deposition on AM in the present study, since soil P data were not available for many of the investigated sites.…”
Section: Discussionmentioning
confidence: 80%
“…Mosse & Phillips (1971) found that, at high P concentrations, roots were colonized only when the medium lacked N. Nevertheless, they did not consider that AMF may be needed for N nutrition. A later connection between P and N availability was established by Sylvia & Neal (1990), who showed that under N‐limiting conditions, P addition had no effect on mycorrhizal colonization whereas, when a sufficient amount of N was supplied, colonization was suppressed by the addition of P. Also Bååth & Spokes (1989) found that only a combination of high P and N concentrations led to reduced mycorrhization.…”
Section: Discussionmentioning
confidence: 97%